Muscle fatigue and interference phenomenon during concurrent aerobic and strength training: An alternative hypothetical model - Denadai, Benedito Sérgio [UNESP]; Greco, Camila Coelho [UNESP] (My University, 2025)
Concurrent training, defined as the combination of strength and aerobic exercise in a periodized program, has been shown to be important in both health and athletic performance contexts. Prescribing concurrent training is challenging because some studies have shown that improvements in strength and muscle mass may be attenuated when compared to strength training alone (i.e., the interference phenomenon). In a previous theoretical model, primarily based on manipulating training intensity, training zones were proposed to either maximize (aerobic training: 95–100 % VO2max + resistance training: 3–4 sets of > 10 maximal repetitions; RM) or minimize (30 to 60 min of moderate-intensity continuous training; MICT + resistance training performed at different % RM) the interference phenomenon. The model proposes that the primary location of adaptations promoted by MICT (i.e., central − cardiovascular) differs from those promoted by strength training protocols (neural and/or peripheral adaptations), thereby attenuating the interference effect on muscle strength. However, there is substantial evidence that the peripheral adaptations (muscle oxidative capacity) from endurance training are not dependent on exercise intensity. In this paper, we propose an alternative hypothetical model of the concurrent training interference phenomenon based on the acute hypothesis (i.e., residual fatigue). We discuss the strengths of the model, considering moderator variables (sex, within-session exercise order, between-mode recovery, endurance training volume, intensity, and modality), which can maximize or minimize the interference phenomenon.
Keywords: Cycling; Exercise intensity; Hypertrophy; Oxidative metabolism; Repetition maximum; Running